2013
DOI: 10.1021/jp4041716
|View full text |Cite
|
Sign up to set email alerts
|

Insensitivity of Tryptophan Fluorescence to Local Charge Mutations

Abstract: The steady state fluorescence spectral maximum (λmax) for tryptophan 140 of Staphylococcal nuclease remains virtually unchanged when nearby charged groups are removed by mutation, even though large electrostatic effects on λmax might be expected. To help understand the underlying mechanism of this curious result, we have modeled λmax with three sets of 50-ns molecular dynamics simulations in explicit water, equilibrated with excited state and with ground state charges. Semiempirical quantum mechanics and indep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 45 publications
4
30
0
Order By: Relevance
“…The large dielectric compensation from bulk water molecules was also found in a previous study by Scott and Callis. 23 The observed screening of bulk water molecule is consistent with the experimentally observed insensitivity of polarity of residues replacing arginine at the position of 58 described above. Moreover, the contribution is largely compensated by an accumulated contribution of many amino acids in the C-terminal half of the protein, which form a β-sheet secondary structure next to PSB half of the chromophore ( Figure S10), and consequently, the overall contribution of the protein comes to be −3.8 kcal/mol, which is smaller than that of the water molecules near PSB, −6.9 kcal/ mol ( Table 1).…”
Section: ■ Resultssupporting
confidence: 85%
“…The large dielectric compensation from bulk water molecules was also found in a previous study by Scott and Callis. 23 The observed screening of bulk water molecule is consistent with the experimentally observed insensitivity of polarity of residues replacing arginine at the position of 58 described above. Moreover, the contribution is largely compensated by an accumulated contribution of many amino acids in the C-terminal half of the protein, which form a β-sheet secondary structure next to PSB half of the chromophore ( Figure S10), and consequently, the overall contribution of the protein comes to be −3.8 kcal/mol, which is smaller than that of the water molecules near PSB, −6.9 kcal/ mol ( Table 1).…”
Section: ■ Resultssupporting
confidence: 85%
“…Water decreases its redshifting influence a full 3500 cm –1 at pH 5 depending on whether Glu27 or Glu42 is protonated, yet protein contributions almost completely compensate that. Exactly the same behavior was found in QM-MM simulations, 50 of the local charge-mutated SNase experiments by Qiu et al; 30 in these and several other cases, 15,2326 a delicate balance between water and protein make the steady state reaction field response to Trp excitation an invariant (Figures S4 and S5, Supporting Information, show dynamics of this compensation).…”
Section: Discussionsupporting
confidence: 79%
“…As noted previously [17], the dipole moment of the 1 La state and the interaction of this state with polar solvents are enhanced by internal CT between the conjugated five-membered pyrrole and six-membered benzene rings, whereas 1 Lb arises mainly from electron redistribution within the benzene unit. The shift in the electron density (ED) from the pyrrole ring to the benzene ring upon excitation to the 1 La state is very sensitive to the environment due to the involvement of the polar nitrogen atom in this transition, as have been confirmed by numerous experimental studies and quantum-mechanical computations [3,53,57].…”
Section: Isolated Chromophore 211 Absorption Structuresmentioning
confidence: 82%
“…These calculated point charges were kept fixed during the MD simulations because the total molecular charge distribution dominates the interaction with other surrounding particles at the VdW distances important for the complexes rather than any minor charge changes on the individual atoms. It has for instance been shown that feeding the QM-calculated point charges back to the MD simulation only lead to minor improvements in the description of the interaction of the indole chromophore with the microenvironment [53].…”
Section: System Preparation and MD Simulationmentioning
confidence: 99%